Lightweight 2D Chaos-Based Encryption Scheme for Secure Image Communication in UAV Applications - Bhargav, Ravi; Singh, Priyanka; Vardhan, P Vishnu (International Conference on Communication Systems and Networks (Online), 2025)
The rapid increase in Unmanned Aerial Vehicles (UAVs) usage in various sectors has highlighted the need for secure image transmission. UAVs act as image-capturing platforms, transmitting data to ground stations and other UAVs over various networks, making the images vulnerable to potential attacks. Secure transmission of these images is crucial to prevent unauthorized access, ensure data integrity, and maintain the confidentiality of sensitive information. To address these challenges, this paper presents a 2D chaos-based encryption method designed to balance security and computational efficiency. The proposed method utilizes a 2D logistic map, reducing computational load while maintaining strong encryption, making it suitable for UAVs with limited resources. The scheme demonstrates high resistance to differential attacks, achieving NPCR and UACI values of 99.6973% and 32.4387%, respectively. Additionally, the high entropy value of 7.97 confirms enhanced randomness and security. The encryption method is evaluated under various attacks, including filtering, compression, and noise, demonstrating robust protection for transmitted images. A comparative analysis was also conducted, which supports the effectiveness of the proposed scheme in terms of reduced computational time and ensure encryption strength.